1991
DOI: 10.1111/j.1399-3038.1991.tb00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated neonatal salivary anti‐casein immunoglobulin A antibodies as an indicator of atopic risk

Abstract: Elevation of salivary SIgA-anti-casein has been shown to occur in newborn infants at risk of allergy. The present study was designed to follow 158 infants over 3 years to relate the onset of clinical disease to SIgA levels at birth. Newborn infants were divided into 3 groups according to their risk of allergy: Group I, (n = 62; no allergy risk); Group 11, (n = 30; low allergy risk); Group 111 ( n = 66; high risk group). The groups were matched for smoking, social background, sex, and dietary habits of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our study, development of allergy during the first 2 years of life tended to be associated with low secretory IgA levels but high levels of total and allergen‐specific IgA. High levels of casein‐specific IgA in saliva have earlier been found at birth in babies who later developed allergy [12]. The Th2 cytokine IL‐4 is important in regulating antibody production, as it activates and induces proliferation of B cells, protects B cells from apoptosis (for review see [13]), and may up‐regulate IgA production [14].…”
Section: Discussionmentioning
confidence: 70%
“…In our study, development of allergy during the first 2 years of life tended to be associated with low secretory IgA levels but high levels of total and allergen‐specific IgA. High levels of casein‐specific IgA in saliva have earlier been found at birth in babies who later developed allergy [12]. The Th2 cytokine IL‐4 is important in regulating antibody production, as it activates and induces proliferation of B cells, protects B cells from apoptosis (for review see [13]), and may up‐regulate IgA production [14].…”
Section: Discussionmentioning
confidence: 70%
“…As IgA does not pass the placenta these antibodies must be of fetal origin and their concentrations should reflect regulatory mechanisms related to the newborn's immune system. In accordance with this concept, Renz et al found a correlation between elevated concentrations of SIgA against casein in the newborn and the subsequent development of atopic disease (3,4).…”
mentioning
confidence: 76%
“…This is an even more controversial area than sensitization via breastfeeding, although there is ample evidence that the human fetus can mount immune responses to in utero allergens from 22 weeks of gestation (Van Asperen et al, 1983;Renz et al, 1991;Piccinni et al, 1993;Jones et al, 1996Jones et al, , 1998Warner et al, 1996). These issues highlight the susceptibility of children to allergenic dietary proteins, the potential risks to children of allergenic proteins even if consumed mostly by adults, and the risk of inducing food allergy in the population by widespread exposure to allergenic GM proteins.…”
Section: Can Genetic Modification Increase the Risk Of Development Ofmentioning
confidence: 99%